Electrodynamics of Metallic Superconductors - Ramazonova Zulxumor (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The theoretical and experimental aspects of the microwave, terahertz, and infrared properties of superconductors are discussed.Electrodynamics can provide information about the superconducting condensate as well as about the quasiparticles. The aim is to understand the frequency dependence of the complex conductivity, the change with temperature and time, and its dependence on material parameters.